Environmental and Legal Regulation of Radioactive Pollution Management - RZABAY, Aktoty; SERIYEV, Bolat; BEISOV, Erbol; KOPBASSAROVA, Gulnurа; KURMANBAYEVA, Damira (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022, 2022)
The article conducts research in the field of radioactive contamination as a problem of natural and man-made emergencies, as a result of which the victims, the preservation of a steady trend of growth in the scale of man-made disasters and the severity of their consequences, are considered as a serious threat to the security of society and the environment, as well as the stability of the development of the ecology of the country. At the same time, the problems of large industrial zones are associated with the concentration of not only potential sources of major radioactive contamination and disasters, but also other environmental industries that are sources of sustainable man-made effects of radiation and chemical factors on the population and the environment. The article discusses the authors' solution to the problems of preventing cases of radioactive contamination, minimising risks and minimising their consequences. The issues of environmental pollution and its impact on public health are considered, and solutions are proposed taking into account the regional characteristics of territories based on a unified methodological approach to assessing the consequences of man-made impacts. Management decisions to prevent cases of radioactive contamination and mitigate their consequences were made in the areas of comprehensive study of sources of pollution and threats of a natural nature, international legal acts on the state of the environment and the circulation of radioactive danger to the life and health of the population, methods for assessing the impact of radioactive and other pollution on the environment and the safety of the population in large industrial regions.